Analysis of Competitive Advantage Factors: Marketing Information System, Digital Marketing and Market Orientation - Setiawan, Jodi (Green Publisher, 2023)
This research was conducted to find out how marketing information systems, digital marketing, and market orientation influence competitive advantage. The method used in this research is quantitative research using literature study or library research methods. The data in this research comes from several national and international journals obtained through trusted platforms such as Science Direct, nelite, scholar, and textbooks or handbooks. The results of this research show that marketing information systems have a positive influence on competitive advantage. Digital marketing, such as online marketing, has a positive and significant influence on competitive advantage. Market orientation has a positive and significant influence on competitive advantage